IN VIVO EVALUATION OF SAFETY AND TOXICITY OF CELL-FREE EXTRACTS CONTAINING ВIFIDOBACTERIUM BIFIDUM AND LACTOBACILLUS REUTERI DERIVATIVES - Knysh, O.V.; Isayenko, O.Yu.; Babych, Ye.M.; Rymsha, O.V.; Pogorila, M.S.; Balak, O.K. (World of Medicine and Biology, 2019)
Evaluation of the toxicity and safety of cell-free extracts, containing biologically active derivatives of Bifidobacterium bifidum and Lactobacillus reuteri, was based on observations of animal behavior, clinical manifestations of toxicity, data of body mass dynamics and lethality. It was shown that all investigated cell-free extracts are non-toxic and are suitable for long-term use if they contain derivatives in a dose corresponding to the daily therapeutic dose of cellular probiotics. The introduction to mice of extracts containing derivatives of probiotics in a dose ten times exceeding the maximum daily human, led to a significant decrease in the mass gain index. The same effect had intraperitoneal and repeated introductions of extracts, especially obtained from bifidobacteria. None of the tested samples exerted a local irritant effect upon intradermal administration.